2009
DOI: 10.1159/000210095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Transcranial Color-Coded Duplex Sonography for Cerebral Artery Stenosis or Occlusion

Abstract: Backgroundand Purpose: Cerebral artery stenosis or occlusion is the most common etiological factor in patients with acute cerebral ischemia, but the rate of early diagnosis is low. The purpose of the study is to evaluate the diagnostic accuracy of transcranial color-coded sonography (TCCS) for cerebral artery stenosis with digital subtraction angiography used as the gold standard of reference. Methods: Seventy-eight patients who were suspected of cerebrovascular disease were involved in the study. Major cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…In previous studies, 2 diagnostic methods (transcranial color-coded sonography versus digital subtraction angiography, CT angiography versus digital subtraction angiography, or magnetic resonance angiography versus digital subtraction angiography) were usually compared. [4][5][6] For example, Klötzsch et al 5 compared the findings in intracranial vessels acquired using transcranial color-coded sonography and digital subtraction angiography in 40 pa-tients and obtained values similar to those in this study (94.2% of displayed vessels; κ = 0.628). Hou et al 4 found a slightly lower correlation between transcranial colorcoded sonography and digital subtraction angiography (κ = 0.56), with sensitivity, specificity, PPV, and NPV values of 72.9%, 82.9%, 78.2%, and 79.4%, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In previous studies, 2 diagnostic methods (transcranial color-coded sonography versus digital subtraction angiography, CT angiography versus digital subtraction angiography, or magnetic resonance angiography versus digital subtraction angiography) were usually compared. [4][5][6] For example, Klötzsch et al 5 compared the findings in intracranial vessels acquired using transcranial color-coded sonography and digital subtraction angiography in 40 pa-tients and obtained values similar to those in this study (94.2% of displayed vessels; κ = 0.628). Hou et al 4 found a slightly lower correlation between transcranial colorcoded sonography and digital subtraction angiography (κ = 0.56), with sensitivity, specificity, PPV, and NPV values of 72.9%, 82.9%, 78.2%, and 79.4%, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…
tenosis and occlusion represent the most frequent abnormalities detected in intracranial arteries. [1][2][3][4][5][6][7][8] Stenosis of an intracranial artery is caused by an atherosclerotic plaque in more than 90% of cases and by a vasospasm, dissection, or vasculitis in less than 10%. Intracranial artery stenosis of atherosclerotic origin is a risk factor for ischemic stroke, [9][10][11] and acute occlusion of intracranial vessels due to atherosclerosis or thrombembolism is the most common cause of stroke.
…”
mentioning
confidence: 99%
“… 54 Colour duplex sonography might be useful for follow-up examinations in patients with cerebral artery stenoses. 113 …”
Section: Therapymentioning
confidence: 99%
“…Transcranial color-coded duplex sonography (TCCS) is widely used to evaluate the intracranial arterial system in patients with acute stroke [1,2,3,4]. There have been insufficient data to compare the ability of ultrasonographic examination to visualize intracranial structures and vessels through the skull bone in different races [5,6,7].…”
Section: Introductionmentioning
confidence: 99%